2015
DOI: 10.1097/brs.0000000000000921
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Vertebral Column Resection for Severe and Rigid Spinal Deformity Associated With Neurological Deficit After Implant Removal Following Posterior Instrumented Fusion

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When all instrumentation is removed for infection, pain, or hardware failure, patients with scoliosis treated with PSF can experience curve progression with an average increase in thoracic deformity of 10°to 23°despite the presence of a solid fusion mass at the time of implant removal [5][6][7]10,11,13 . In some instances, severe curve progression after implant removal has required revision PSF with instrumentation to correct the deformity [14][15][16] . Although the presence of infection may predispose patients to the development of a subclinical pseudarthrosis, Alpert et al found that for patients without infection, deformity still increased an average of 19°after implant removal, compared with an average of 34°in the infected cohort 6 .…”
Section: Discussionmentioning
confidence: 99%
“…When all instrumentation is removed for infection, pain, or hardware failure, patients with scoliosis treated with PSF can experience curve progression with an average increase in thoracic deformity of 10°to 23°despite the presence of a solid fusion mass at the time of implant removal [5][6][7]10,11,13 . In some instances, severe curve progression after implant removal has required revision PSF with instrumentation to correct the deformity [14][15][16] . Although the presence of infection may predispose patients to the development of a subclinical pseudarthrosis, Alpert et al found that for patients without infection, deformity still increased an average of 19°after implant removal, compared with an average of 34°in the infected cohort 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Suk et al 17) have introduced posterior VCR (PVCR) procedure. Thereafter several researchers reported the outcomes following PVCR sequentially 12 , 17 , 18 , 20) . The PVCR has purposed at the decrease of complications and technical difficulties of the traditional anterior-posterior VCR 17) .…”
Section: Introductionmentioning
confidence: 99%